Blood Glukose Response of Giant Gouramy (Osphronemus gaouramy, Lac.) to the Stress of Environmental Temperature Changes - Hastuti, S.; Supriyono, Eddy; Mokoginta, Ing; Subandiyono, . (Indonesian Society of Scientific Aquaculture (ISSA), 2003)
This experiment was conducted to investigate blood glucose performance of giant gouramy (Osphronemus gouramy, Lac.) to environmental changes. Fish with body weight of about 52,15 g was used in the experiment. A hundred and twenty fish were subjected to stress by moving them to another aquarium containing cooler water for 5 minute before put them back to the origin aquarium. The stress treatments were Δ 0°C (A), Δ-3°C (B), Δ-6°C(C), and Δ-9°C(D). Blood glucose was measured at 0, 1, 2, 3, 4 and 5 hours post stress, each for 5 fish. During stress treatment, the survival offish were recorded. To study the role of insulin activation on reducing the stress effects, thirty fish were injected with insulin 2 IU/100 g body weight before subjected them to stressar. Blood glucose level of fish subjected to temperature stress of Δ-9°C was the greatest. The blood glucose response to temperature changes was linear, Y = 4,4543 X + 35,553 with R2 = 0,09976. The survival rate of fish was 100% for all treatments. Injected of insulin 2 IU/100 g body weight was able to reduce hyperglycemia that caused by stress. Key words: Blood glucose, giant gouramy, Osphronemus gouramy, stress ABSTRAK Penelitian ini dilakukan dengan tujuan untuk mengetahui performa glukosa darah ikan gurami (Osphronemus gouramy, Lac.) dalam merespon perubahan suhu lingkungan. Ikan berbobot rata-rata 52,15 g sebanyak 120 ekor diberi stres dengan cara diangkat dan dipindahkan ke suatu wadah yang bersuhu lebih dingin selama 5 menit dan dikembalikan lagi ke wadah mula-mula. Perlakuan stres perubahan suhu dingin tersebut adalah A (Δ 0°C), B (Δ- 3°C), C (Δ-6°C) dan D (Δ-9°C). Glukosa darah diukur dari 5 ekor ikan pada jam ke 0, 1, 2, 3, 4 dan 5 jam pascastres. Kelangsungan hidup dihitung pada saat perlakuan stres. Untuk melihat peran aktivasi insulin dalam menekan efek stres, ikan sebanyak 30 ekor diinjeksi insulin 2 iu/100 g bobot badan sebelum diberi stres. Kadar glukosa darah ikan gurame yang diberi stres perubahan suhu dingin sebesar Δ-9°C mengalami peningkatan paling besar. Respon glukosa darah terhadap stres perubahan suhu tersebut berpola linier Y= 4,4543 X + 35,553, dengan R2 = 0,9976. Perlakuan tersebut menghasilkan kelangsungan hidup yang sama yaitu 100%. Injeksi insulin 2 IU/100 g bobot badan mampu menekan hiperglisemia akibat stres. Kata kunci: Glukosa darah, ikan gurami, Osphronemus gouramy, stres